2022
DOI: 10.1101/2022.08.10.22278649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining and phenotyping gastric abnormalities in long-term type 1 diabetes using body surface gastric mapping

Abstract: Objective: To define phenotypes of gastric myoelectrical abnormalities and relation to symptoms in people with longstanding T1D, compared to matched healthy controls, using a novel non-invasive body surface gastric mapping (BSGM) device. Research design and methods: BSGM was performed on people with T1D of >10 years duration and matched controls, employing Gastric Alimetry (Alimetry, New Zealand), comprising a high-resolution 64-channel array, validated symptom logging App, and wearable reader. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(57 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…To this end, group-level differences have recently been established between symptomatic type 1 diabetics and controls for the GA-RI and Principal Gastric Frequency, and the amplitude. 32 Further studies evaluating the revised metrics in patient populations are the subject of ongoing work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, group-level differences have recently been established between symptomatic type 1 diabetics and controls for the GA-RI and Principal Gastric Frequency, and the amplitude. 32 Further studies evaluating the revised metrics in patient populations are the subject of ongoing work.…”
Section: Discussionmentioning
confidence: 99%
“…the onset and duration of this response. 13,16,32 Therefore, if meal response metrics employ only a brief fixed window (e.g. 21 ), meal responses may be underestimated.…”
Section: Gastric Alimetry Rhythm Index (Ga-ri) (Unitless)mentioning
confidence: 99%
See 1 more Smart Citation
“…Promising data has recently been reported in this regard, indicating the capability of gastric mapping to separate nausea and vomiting patients into subgroups with neuromuscular abnormalities vs normal electrophysiology, the latter being more likely to experience disorders of gut‐brain interaction 14 . In addition, three studies have now indicated symptom correlations based on gastric mapping phenotypes in nausea and vomiting disorders, FD, and diabetes 14,34,35 …”
Section: Gastric Myoelectrical Activitymentioning
confidence: 99%
“…14 In addition, three studies have now indicated symptom correlations based on gastric mapping phenotypes in nausea and vomiting disorders, FD, and diabetes. 14,34,35 An attraction of body surface gastric mapping is that the emerging disease phenotypes, such as neuromuscular dysfunction, appear to represent more direct mechanisms than higher-order variables such as delayed transit. However, body surface gastric mapping has only recently emerged, and its role in diagnostic and therapeutic pathways will become clearer with further data and development.…”
Section: G a S Tri C Myoelec Tri C Al Ac Tivit Ymentioning
confidence: 99%